Comparison of fluoroscopically guided and blind corticosteroid injections for greater trochanteric pain syndrome: multicentre randomised controlled trial. (14th April 2009) - Cohen, Steven P; Strassels, Scott A; Foster, Leslie; Marvel, John; Williams, Kayode; Crooks, Matthew; Gross, Andrew; Kurihara, Connie; Nguyen, Cuong; Williams, Necia
Abstract : Objective To determine whether fluoroscopic guidance improves outcomes of injections for greater trochanteric pain syndrome. Design Multicentre double blind randomised controlled study. Setting Three academic and military treatment facilities in the United States and Germany. Participants 65 patients with a clinical diagnosis of greater trochanteric pain syndrome. Interventions Injections of corticosteroid and local anaesthetic into the trochanteric bursa, using fluoroscopy (n=32) or landmarks (that is, "blind" injections; n=33) for guidance. Main outcome measures Primary outcome measures: 0-10 numerical rating scale pain scores at rest and with activity at one month (positive categorical outcome predefined as ≥50% pain reduction either at rest or with activity, coupled with positive global perceived effect). Secondary outcome measures included Oswestry disability scores, SF-36 scores, reduction in drug use, and patients' satisfaction. Results No differences in outcomes occurred favouring either the fluoroscopy or blind treatment groups. One month after injection the average pain scores were 2.7 at rest and 5.0 with activity in the fluoroscopy group compared with 2.2 and 4.0 in the blind injection group. Three months after the injection, 15 (47%) patients in the blind group and 13 (41%) in the fluoroscopy group continued to have a positive outcome. Conclusion Although using fluoroscopic guidance dramatically increases treatment costs for greater trochanteric pain syndrome, it does not necessarily improve outcomes. Trial registration Clinical trials NCT00480675